If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3 + -2x = 4 + 2x Solving 3 + -2x = 4 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 3 + -2x + -2x = 4 + 2x + -2x Combine like terms: -2x + -2x = -4x 3 + -4x = 4 + 2x + -2x Combine like terms: 2x + -2x = 0 3 + -4x = 4 + 0 3 + -4x = 4 Add '-3' to each side of the equation. 3 + -3 + -4x = 4 + -3 Combine like terms: 3 + -3 = 0 0 + -4x = 4 + -3 -4x = 4 + -3 Combine like terms: 4 + -3 = 1 -4x = 1 Divide each side by '-4'. x = -0.25 Simplifying x = -0.25
| 3(-2)+4=5-6 | | -5(1-2x)=8 | | ln(7x^2-3)=2 | | 10(-3-2t)+10-12t+26=0 | | x-7=7-x | | -7x+4=x | | 0=2x-17 | | 5-9+=6+2-3 | | -7(x+3)-10=31+1 | | -3z-8=10 | | 10x-5x-3=-2 | | 9-8=8 | | 4x^4-12x^3+3=0 | | 5(4x-3)+x=7(3x+2) | | -2y-13=6y+19 | | -8(x-2)+2=58 | | 9y+12y=63 | | 7x=96-x | | -2(11-4c)=11(c-8) | | 9y+7.7=-4.5 | | 8(-2)=16 | | 5y+7=62 | | 4(x+12)-5=79 | | (x-1)(3x-5)(4x-8)=0 | | X-5=9x-9 | | 1/2=78 | | 7.87=26.25+.5a(2.5) | | 124-5x=40x+19 | | 3x^2-6=6y | | 7.87=26.25+.5(2.5) | | -5(x+7)-42=2-49 | | -5-4=21 |